STRES DAN KECEMASAN ATLET SEBELUM PERTANDINGAN - S, Adi; Aliriad, Hilmy; Wira Yudha Kusuma, Donny; Arbanisa, Wahyu; Winoto, Ahmad (Indonesian Journal of Physical Education and Sport Science, 2024)
Studi purpose. Stress and anxiety are every day for athletes, but they need severe treatment. Pre-match anxiety is often present and quite disruptive to an athlete's performance. Anxiety is inherent in sports and may be experienced at all levels. This study examines the effects of stress and anxiety before the match. Materials and methods. This study used the article review method by collecting qualitative and quantitative data through reputable journal articles. This article reviewed the literature on athlete stress and anxiety leading to a match. Research with this article review method used relevant and accurate data to be used as material for readers. Results. The results of the review concluded that athletes who experienced high levels of stress have the effect of a 70% higher risk of injury, and increased anxiety could harm athlete performance during matches. The causes of anxiety in athletes before competing included competitive anxiety, cognitive anxiety, and somatic anxiety. Conclusions. In conclusion, athletes will experience symptoms of anxiety and stress in the match due to various things, such as the presence of thousands of spectators who can threaten the athlete's self-esteem and the negative judgment of the community towards losing athletes.